GOBIATIDS (ANURA) FROM THE UPPER CRETACEOUS LOCALITY KHERMEEN-TSAV (GOBI DESERT, MONGOLIA) - Gubin Y.M. (My University, 1999)
A new genus and species Cretasalia tsybini (Gobiatidae, Anura) from the Late Cretaceous (Campanian-Maastrichtian) locality Khermeen-Tsav (South Gobi Region, Mongolia) is described from a skull and part of the skeleton. Cretasalia is characterized by large pointed skull, almost total absence of dermal bone sculpturing, low maxillary and high frontal process. The diagnosis of the genus Gobiates is amended and distinctivness of G. khermeentsavi is demonstrated. Phylogenetically the Gobiatidae are close to the Pelobatidae and more distantly related to the Discoglossidae.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая